2021
DOI: 10.1111/cid.12994
|View full text |Cite
|
Sign up to set email alerts
|

Long term clinical performance of 10 871 dental implants with up to 22 years of follow‐up: A cohort study in 4247 patients

Abstract: Background The present retrospective study was aimed to assess the long‐term clinical performance of dental implants in a cohort study of 4247 patients. Methods A longitudinal observational cohort study was done on all implants performed by a single periodontist from July 1995 to April 2019. The main outcome variables of this study were implant failure and marginal bone level around implants. Results The study participants received a total of 10 871 implants with a mean of 2.56 implants per patient. The cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 17 publications
1
65
1
Order By: Relevance
“…The structure of sternum resembles the upper jaw. The failure rate of implants was calculated as 17% in this study, which is higher than that reported in usual conditions (11)(12)(13). However, it has been demonstrated that the degree of implant failure is high in grafted bone and may even reach 25% in extensive defects.…”
Section: Discussioncontrasting
confidence: 60%
“…The structure of sternum resembles the upper jaw. The failure rate of implants was calculated as 17% in this study, which is higher than that reported in usual conditions (11)(12)(13). However, it has been demonstrated that the degree of implant failure is high in grafted bone and may even reach 25% in extensive defects.…”
Section: Discussioncontrasting
confidence: 60%
“…Five studies showed no negative influence [ 10 , 11 , 38 , 42 , 44 ], two showed a non-significant [ 29 , 36 ] and six a significantly negative influence of diabetes on implant survival [ 12 , 16 , 32 , 37 ]. For example, the study of Alberti et al [ 38 ] showed no significant difference of the implant survival after 10 years in patients with diabetes (survival rate of 96.5%) compared to patients without diabetes mellitus (survival rate of 94.8%), whereas the study of French et al [ 37 ] identified diabetes mellitus with a hazard ratio of 2.25 as a risk factor for implant failure in a multivariate analysis, implicating an over two times higher risk for failure of dental implants in patients with diabetes mellitus. In addition, eight aggregated literature references could be included on this question, whereby in seven publications, it was concluded that diabetes mellitus does not seem to have a significant influence on implant survival [ 8 , 51 , 52 , 55 58 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Patients with uncontrolled diabetes mellitus were reported to be at a greater risk for developing peri-implant diseases (7,22,57,58). In a recent meta-analysis, diabetic patients were at 1.46 times greater risk for developing peri-implantitis than non-diabetic patients (57).…”
Section: Diabetes Mellitusmentioning
confidence: 99%